Development of immunoassays for detecting oxyfluorfen residue in agricultural and environmental samples. Issue 9 (30th January 2018) - Sheng, Enze; Du, Mei; Yang, Jiachuan; Hua, Xiude; Wang, Minghua
Abstract : An enzyme-linked immunosorbent assay (ELISA) and chemiluminescent immunoassays (CLEIA) were developed to detect oxyfluorfen in agricultural and environmental samples. Abstract : An enzyme-linked immunosorbent assay (ELISA) and chemiluminescent immunoassays (CLEIA) were developed to detect oxyfluorfen in agricultural and environmental samples. The hapten of oxyfluorfen was synthesized and conjugated with bovine serum albumin (BSA) and ovalbumin (OVA) to produce immunogen and coating antigen. One cell line (1A7D6F5) that stably secretes anti-oxyfluorfen monoclonal antibody (mAb) is obtained by cell fusion. Under optimal conditions, the half-maximal inhibition concentration (IC50 ) and the limit of detection (LOD, IC20 ) of ELISA are 0.065 mg L −1 and 0.0048 mg L −1, while those of CLEIA are 0.021 mg L −1 and 0.0016 mg L −1, respectively. The immunoassays show no obvious cross-reactivities with the analogues of oxyfluorfen except for benzofluorfen and bifenox. The recoveries of oxyfluorfen in the spiked samples of soil, grape, peach, apple and pear are in the range of 74.1–107.2% with a RSD of 2.7–9.7% for ELISA, and 77.2–106.4% with a RSD of 2.4–7.9% for CLEIA. The results of immunoassays for the authentic samples are significantly correlated with those detected by gas chromatography (GC).